2018
DOI: 10.1093/ckj/sfy013
|View full text |Cite
|
Sign up to set email alerts
|

Daprodustat for anemia: a 24-week, open-label, randomized controlled trial in participants with chronic kidney disease

Abstract: BackgroundThis study assessed the short-term safety and efficacy of daprodustat (an oral hypoxia-inducible factor-prolyl hydroxylase inhibitor) to achieve a target hemoglobin in patients with anemia of chronic kidney disease (CKD).MethodsPatients (n = 252) with Stages 3–5 CKD not receiving dialysis were enrolled in this 24-week, multicenter trial [hemoglobin entry criteria: 8–10 g/dL (Cohort 1) or 8–11 g/dL (Cohort 2) for recombinant human erythropoietin (rhEPO)-naïve participants; 9–10.5 g/dL (Cohort 1) or 9–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
82
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 25 publications
5
82
0
1
Order By: Relevance
“…HIF-PHIs stimulate erythropoiesis by inhibiting HIFprolyl hydroxylases (PHD1, PHD2, PHD3), leading to activation of HIF-responsive genes that regulate the tissue response to hypoxia, including the EPO gene and genes involved in iron homeostasis (14). In a phase 2 study in anemic patients with stages 3 to 5 CKD who were rhEPO naïve or had switched from existing rhEPO therapy, daprodustat increased and effectively maintained target hemoglobin levels within a narrow prespecified range over 24 weeks without any adverse trends reported (15). Another phase 2 study in hemodialysis patients showed that daprodustat 4 to 10 mg once daily produced dosedependent changes in hemoglobin levels over the first 4 weeks after patients were switched from a stable dose of rhEPO.…”
mentioning
confidence: 99%
“…HIF-PHIs stimulate erythropoiesis by inhibiting HIFprolyl hydroxylases (PHD1, PHD2, PHD3), leading to activation of HIF-responsive genes that regulate the tissue response to hypoxia, including the EPO gene and genes involved in iron homeostasis (14). In a phase 2 study in anemic patients with stages 3 to 5 CKD who were rhEPO naïve or had switched from existing rhEPO therapy, daprodustat increased and effectively maintained target hemoglobin levels within a narrow prespecified range over 24 weeks without any adverse trends reported (15). Another phase 2 study in hemodialysis patients showed that daprodustat 4 to 10 mg once daily produced dosedependent changes in hemoglobin levels over the first 4 weeks after patients were switched from a stable dose of rhEPO.…”
mentioning
confidence: 99%
“…Another 24-week, randomized, open-label, multicentre, phase 2b study (NCT01977573) showed that daprodustat effectively achieved/maintained target Hb levels over 24 weeks in non-dialysis-dependent CKD-3/4/5 patients with anaemia who were rhEPO naïve or who had switched from existing rhEPO therapy [18]. Patients who were rhEPO naïve (n = 180) were randomized 3:1 to receive daprodustat (1, 2 or 4 mg based on baseline Hb) once daily or control (rhEPO per standard of care), and rhEPO-users (n = 72) were randomized 1:1 to daprodustat 2 mg once daily or control (rhEPO per standard of care) for 4 weeks, thereafter daprodustat doses could be adjusted to achieve and maintain target Hb levels (9-10.5 g/dL in Cohort 1 and 10-11.5 g/dL in Cohort 2).…”
Section: Phase 2 Studiesmentioning
confidence: 99%
“…Top-cited articles also included those related to CKD complications, such as cognitive function [ 6 ] and frailty [ 12 ], as well as management of complications such as pain [ 4 ] and anaemia [ 32 , 38 ]. Anaemia management focused on early clinical trials the novel drug family of oral hypoxia-inducible factor activators, such as daprodustat [ 32 , 38 ].…”
Section: Ckd Complications and Their Managementmentioning
confidence: 99%